RELIGIOUS HARMONY THROUGH THE DEVELOPMENT OF HOUSE OF WORSHIP BASED ON LOCAL GENIUS IN KEI ISLANDS, MALUKU - Sabara Nuruddin; Aksa Aksa (Al-Qalam, 2022)
The establishment of houses of worship represents how religious harmony exists in a community. The practice of harmony in the establishment of a house of worship shows the harmonization of relations between people in the community. This study explores cases of the practice of harmony through the establishment of a house of worship based on local wisdom that occurred in the Kei Islands, Maluku. The problems studied include; a description of the practice of harmony in the establishment of houses of worship, optimizing the function of local wisdom in the establishment of houses of worship and the participation of various elements of society related to harmony through the establishment of houses of worship based on local wisdom. Qualitative-descriptive research with a case study approach. The case of the chosen house of worship is the establishment of the Al-Manafi Mosque, Dian Pulau (Ohoi) Village, Hoat Sorbay District, Southeast Maluku. Field findings indicate the practice of harmony in the construction of the mosque because it involves the active participation of various elements of interfaith society. In the committee structure of the mosque establishment, there are even 15 names of non-Muslim committee members. Local wisdom functions optimally as the basis that forms the practice of this harmony. Kei's local wisdom, starting from the philosophy of ain ni ain, the customary law of Larvul Ngabal, the spirit of fanganan, to the practical forms of maren (gotong royong) and yelim (helping each other) optimally work to build collective awareness and the driving force that overcomes differences in faith, until the realization of the practice of harmony. All elements and levels of society, both individually and in groups, as well as the government, gave active participation in the establishment of the Al-Manafi Mosque, so as to create the practice of harmony among religious believers through the establishment of the house of worship.